2021
DOI: 10.1007/jhep10(2021)070
|View full text |Cite
|
Sign up to set email alerts
|

A CFT distance conjecture

Abstract: We formulate a series of conjectures relating the geometry of conformal manifolds to the spectrum of local operators in conformal field theories in d > 2 spacetime dimensions. We focus on conformal manifolds with limiting points at infinite distance with respect to the Zamolodchikov metric. Our central conjecture is that all theories at infinite distance possess an emergent higher-spin symmetry, generated by an infinite tower of currents whose anomalous dimensions vanish exponentially in the distance. State… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 137 publications
(247 reference statements)
2
52
0
Order By: Relevance
“…Instead, they treat a fixed CFT irrespective of its deformations. New methods are needed to take advantage of the vast additional data encoded elsewhere in the conformal manifold, and to address questions about the manifold itself, such as whether there are universal properties of CFTs at infinite distance [204]. See [205][206][207] for recent works exploring conformal manifolds from the bootstrap perspective.…”
Section: Conformal Manifolds and Deformationsmentioning
confidence: 99%
“…Instead, they treat a fixed CFT irrespective of its deformations. New methods are needed to take advantage of the vast additional data encoded elsewhere in the conformal manifold, and to address questions about the manifold itself, such as whether there are universal properties of CFTs at infinite distance [204]. See [205][206][207] for recent works exploring conformal manifolds from the bootstrap perspective.…”
Section: Conformal Manifolds and Deformationsmentioning
confidence: 99%
“…Another interesting direction for future research involves the classification of weak coupling limits, as initiated in e.g. [44,110,112,89,115,113,114]. The Emergent String Conjecture of [112], in particular, suggests that any infinite distance/weak coupling limit must be either a decompactification limit or an emergent string limit, in which a fundamental string becomes tensionless.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in compactifications of M-theory to 5d, it has been shown that every point of vanishing gauge coupling is at infinite distance in moduli space [111]. An analogous statement holds in the context of AdS/CFT: in any SCFT in d > 2 dimensions, every point on the conformal manifold at which some sector of the theory becomes free is at infinite distance in the Zamolodchikov metric [115]. This translates to the statement that the vanishing of a gauge coupling must occur at infinite distance in the moduli space of the bulk AdS dual theory.…”
Section: Relation To the Swampland Distance Conjecturementioning
confidence: 91%
“…Let us conclude by noting that for cases in which one of the Coulomb branch scaling dimensions is ∆ u i = 2, the theory has an exactly marginal operator parameterizing a conformal manifold. In [85,86] it was conjectured that any N = 2 n-dimensional conformal manifold arises by gauging n simple factors in the global symmetry of isolated N = 2 SCFTs. This means that if ∆ u i = 2 the corresponding theory is either Lagrangian, or an SU(2) conformal gauging of a lower rank theory.…”
Section: B Allowed Rank-two Coulomb Branch Dimensionsmentioning
confidence: 99%